PRODUKSI KITINASE EKSTRASELULER Aspergillus rugulosus 501 SECARA OPTIMAL PADA MEDIA CAIR - Widhyastuti, Nunuk (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Chitinases hydrolyzing chitin are produced by various organisms and their physiological functions depend on their sources.Chitinases and its hydrolysis products have a broad range of applications. Increasing commercial interest in chitinase and its products has led to the need of inexpensive, reliable sources of active and stable chitinase preparations.The activity of chitinase produced by Aspergillus rugulosus 501 in liquid culture and the parameters that controlled the enzyme synthesis were studied to find optimal conditions for the enzyme production. Hydrolysis products of chitinase were detected by Reissig method. The results showed that fungal chitinase activity in media containing organic nitrogen and phosphate was higher than that in media containing trace element, organic and anorganic nitrogen but lack of phosphate. The maximum enzyme activity reached in the second day incubation.Chitinase production was affected by the initial pH of media, chitin consentration and source of nitrogen, while the consentrasion of inoculum used in this study did not affect enzyme production. High enzyme activity was found in media with initial pH 5.0-6.5. When using different consentration of colloidal chitin, chitinase activities were also found high in concentration from 0.75% tol .5%. The organic nitrogen sources gave the better results compared to the anorganic ones.